The “cardiac neglect”: a gentle reminder to radiologists interpreting contrast-enhanced abdominal MDCT - Talakić, Emina; Schöllnast, Helmut; Kaufmann-Bühler, Ann-Katrin; Hohenberg, Florian; Mijović, Ksenija; Nagy, Eszter; Fuchsjäger, Michael; Tschauner, Sebastian (Frontiers in Cardiovascular Medicine, 2023)
Myocardial infarction (MI) may be visible on contrast-enhanced multidetector computed tomography (MDCT) scans of the abdomen. In the previous literature, potentially missed MI in abdominal MDCTs was not perceived as an issue in radiology. This retrospective single-center study assessed the frequency of detectable myocardial hypoperfusion in contrast-enhanced abdominal MDCTs. We identified 107 patients between 2006 and 2022 who had abdominal MDCTs on the same day or the day before a catheter-proven or clinically evident diagnosis of MI. After reviewing the digital patient records and applying the exclusion criteria, we included 38 patients, with 19 showing areas of myocardial hypoperfusion. All MDCT studies were non ECG-gated. The delay between the MDCT examination and MI diagnosis was shorter in studies with myocardial hypoperfusion (7.4±6.5 hours and 13.8±12.5 hours) but not statistically significant p=0.054. Only 2 of 19 (11%) of these pathologies had been noted in the written radiology reports. The most common cardinal symptom was epigastric pain (50%), followed by polytrauma (21%). STEMI was significantly more common in cases of myocardial hypoperfusion p=0.009. Overall, 16 of 38 (42%) patients died because of acute MI. Based on extrapolations using local MDCT rates, we estimate several thousand radiologically missed MI cases worldwide per year.